Respuesta :
The answer would be -6g/5.
6f+9g=3g+f
5f+9g=3g
5f=-6g
---------
5
f=-6g/5 (-6g over 5)
6f+9g=3g+f
5f+9g=3g
5f=-6g
---------
5
f=-6g/5 (-6g over 5)
Answer:
f= -(6/5)g
Explanation:
We have been given the expression 6f+9g = 3g+f
Solve for f means find the value of f
We will simplify the given expression:
we will collect the values of f at one side and g on the other side
So, rewriting the given expression 6f+9g =3g+f as 6f-f=3g-9g
So, after simplification it will lead to 5f= -6g
After further simplification f= -(6/5)g which is the final result